Age influence on resistance and deformation of the human sutured meniscal horn in the immediate postoperative period - Peña-Trabalon, Alejandro; Perez-Blanca, Ana; Moreno-Vegas, Salvador; Estebanez Campos, M. Belen; Prado-Novoa, Maria (Frontiers in Bioengineering and Biotechnology, 2024)
Introduction: To preserve knee function, surgical repair is indicated when a meniscal root disinsertion occurs. However, this surgery has not yet achieved complete recovery of the joint´s natural biomechanics, with the meniscus-suture interface identified as a potentially determining factor. Knowing the deformation and resistance behavior of the sutured meniscal horn and whether these properties are preserved as the patient ages could greatly contribute to improving repair outcomes.Methods: A cadaveric experimental study was conducted on human sutured menisci classified into three n=22 age groups (young ≤ 55; 55 < middle-aged ≤ 75; 75 < old) were subjected to load-tofailure test by suture pulling. Meniscal thickness at the suture hole was measured and the applied traction force and tissue deformation in the suture area in the direction of traction were recorded during the test. The traction load that initiated the meniscal cut-out, 𝐹𝑐, maximum load borne by the meniscus, 𝐹𝑢, tissue stress at the cut-out initiation, 𝑆𝑐, and equivalent stiffness modulus at the suture area, 𝑚𝑠, were calculated.Results: At the tissue level, the resistance in terms of 𝑆𝑐 decrease with age (young: 47.2 MPa; middle-aged: 44.7 MPa; old: 33.8 MPa) being significantly different between the young and the old group (p=0.015). Mean meniscal thickness increased with age (young: 2.50mm; middle-aged: 2.92mm; old: 3.38mm; p=0.001). Probably due to thickening, no differences in resistance were found at the specimen level i.e., in 𝐹𝑐 (overall mean 58.2N) and 𝐹𝑢 (overall mean 73.6N). As for elasticity, 𝑚𝑠 was lower in the old group than in the young group (57.5MPa vs. 113.6MPa, p=0.02) and the middle-aged one (57.5MPa vs. 108.0MPa, p=0.04).Regarding the influence of age on the sutured meniscal horn tissue, in vitro experimentation revealed that meniscal horn specimens older than 75 years old had a more elastic tissue which was less resistant to cut-out than younger menisci at the suture hole area. However, a thickening of the meniscal horns with age, which was also found, leveled out the difference in the force that initiated the tear, as well as in the maximum force borne by the meniscus in the load-to-failure test.